Traditional Wisdom and Policy Formulation in Bayung Gede Village, Bali Province - Soediro, Dian; Suciyanti (Moccasin Journal De Public Perspective, 2025)
Traditional wisdom has been a cornerstone of governance and community practices in many indigenous villages, yet its integration into modern policy-making remains a complex challenge. This study examines the role of traditional wisdom in policy formulation in Bayung Gede Village, Bali, focusing on agriculture, environmental management, and governance. Through qualitative methods, including semi-structured interviews and participatory observation, the research investigates how local governance systems and traditional agricultural practices contribute to sustainability. The findings show that traditional governance, rooted in spiritual beliefs and collective decision-making, fosters community cohesion and ecological balance. Traditional agricultural practices, such as organic farming and communal irrigation systems, support long-term environmental sustainability. However, the study also reveals the challenges of integrating these practices into contemporary policy frameworks that prioritize economic growth and efficiency. The study concludes that incorporating traditional wisdom into modern policy can enhance sustainability and promote more inclusive, culturally appropriate development strategies. The research contributes to the body of knowledge on the integration of indigenous knowledge into policy-making, highlighting the potential for bridging the gap between traditional and modern governance. Future research could focus on evaluating the effectiveness of such integration in other rural communities and examining its impact on sustainable development.